2018
DOI: 10.15171/hpr.2018.04
|View full text |Cite
|
Sign up to set email alerts
|

Medical Errors Disclosure: Is It Good or Bad?

Abstract: Background: In the treatment and health process, there are a lot of dangers to patients, and the increased number of medical errors is one of the most important circumstances of this process. Objective: The present research purposed to decrease medical errors through disclosure of them in hospitals of Tehran University of Medical Sciences. Methods: This qualitative-quantitative study included a population of 232 individuals, selected through targeted non-random selection, who were somehow connected with medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Ten common recommendations for reducing/eliminating medical errors are provided in Table 5 [58]. Meanwhile, the errors should be disclosed without considering the consequences from blaming, negative emotions, expectations, and so forth in order to perform better management of these cases, refer to Figure 7 [63].…”
Section: Care Flow Processmentioning
confidence: 99%
“…Ten common recommendations for reducing/eliminating medical errors are provided in Table 5 [58]. Meanwhile, the errors should be disclosed without considering the consequences from blaming, negative emotions, expectations, and so forth in order to perform better management of these cases, refer to Figure 7 [63].…”
Section: Care Flow Processmentioning
confidence: 99%
“…In line with our findings, two former studies reported the organizational culture of error communication among the most important factors affecting error communication in healthcare organizations. 38,39 A study reported that inappropriate organizational characteristics such as poor safety guidelines, low error intolerance threshold, lack of team-based accountability, person-centered approach to errors, blame and reproach culture, inappropriate managerial reaction to errors, and incongruence between error severity and error-related reactions can make staff hide their errors. 40…”
Section: The Culture Of Error Communicationmentioning
confidence: 99%
“…56 Another study also showed that nurses’ professional characteristics such as professional commitment, accountability, and inter-professional relationships indirectly facilitate or interfere with error communication. 39…”
Section: Ethical and Professional Characteristicsmentioning
confidence: 99%